PENGENALAN CITRA BATIK MENGGUNAKAN METODE CELLULAR AUTOMATA - Amanda Larasati; Bambang Heru Iswanto; Iwan Sugihartono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The identification of three Batik profile, i.e Batik Parang, Megamendung, and Sidomukti have been done by using Cellular automata method. Cellular automata 56 method was used to identify the edge of binaries batik profile from each of ethnics. The first step is batik profile examined using convolution technique. In this technique we multiply 8 matrices of 3 x 3 with profile pixels. The highest results which were accounted by mean value from 3 x 3 matrices from one profile are represented by pixel. The results shows batik Megamendung has CA5 less than 0.09, Batik Parang has CA5 and CA6 between 0.5-2.63 and CA1 larger than CA4 and Batik Sidomukti has CA3 and CA4 larger than 11.40 and CA4 larger than CA1. Therefore, Cellular method can be identifying batik profile with efficiency of 76%. Keywords: batik profile, Cellular automata, Batik Parang, Megamendung, and Sidomukti.